Competitive strategies and value creation: a twofold perspective analysis. Issue 10 (7th October 2014) - Teti, Emanuele; Perrini, Francesco; Tirapelle, Linda
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate whether the implementation of a defined competitive strategy – differentiation or cost leadership – brings about different value creation levels, where "value" is defined in a twofold perspective as "shareholder value" vs "stakeholder value" and "social capital". Design/methodology/approach – A sample of 169 European companies is investigated. Simple linear regressions and t-tests for the equality of means are conducted. Findings – While no significant differences are found in the creation of value for the shareholders, firms following differentiation strategies generate considerably higher value for all the stakeholder groups than companies pursing cost leadership strategies. Results also show that size and reputational considerations play a significant role in explaining the different stakeholder value performances. Research limitations/implications – Some data such as off-balance sheet items could have influenced the calculation of the discriminant values for strategy classification. Practical implications – Although the two groups manage to achieve comparable levels of profitability, the differentiators, presumably because of their structural outward-facing orientation, seem to be better positioned to meet the challenges of the next wave of growth, which resides in the substantial interconnection between economic and societal value. Companies need a better understanding of how the stakeholder value theory and social capital can influence value creation and long-term success. Originality/value – In light of the importance of competitive strategy as a value-creation tool, the paper sheds new light on the relationship between competitive strategies and value creation.